In vitro fertilization-induced extreme hypertriglyceridemia with secondary acute pancreatitis in emergency department: A case report and literature review - Nguyen Huu Thanh; Trinh Van Duong; Nguyen Thu Huyen; Pham Dang Hai (Turkish Journal of Emergency Medicine)
Acute pancreatitis is one of the severe complications of hypertriglyceridemia, which needs to be recognized early to provide appropriate treatment. Hypertriglyceridemia-induced pancreatitis has several causes, in which in vitro fertilization (IVF) is a rare etiology that is becoming increasingly popular. We report a 33-year-old female patient with a history of hypertension who has failed an IVF cycle and started a new IVF procedure 1 month before admission. She was diagnosed with severe triglyceridemia-induced acute pancreatitis with extremely high serum triglycerides (TGs) levels (18,547 mg/dL). We combined plasmapheresis and intravenous (IV) insulin and significantly reduced blood TG over a short time. She was discharged with a TG level of 366.7 mg/dL on the 10th day. It is essential to monitor serum TG levels in plasma before, during, and after this therapy, especially in the 1st month after initiating IVF. Although plasmapheresis combined with IV insulin is not officially recommended for acute triglyceridemia-induced pancreatitis, the therapy can be considered in cases with extremely high serum TG levels.